Quantification of Uncertainties of Future Climate Change: Challenges and Applications. - Mearns, Linda O. (Philosophy of Science, 2010)
Increasing societal concerns regarding the potential deleterious effects of future climate change have galvanized efforts to manage the problem both through reduction of greenhouse gases (mitigation) and through development of plans to reduce the impacts of climate change that cannot be avoided (adaptation). These critical activities require making decisions under conditions of considerable uncertainty regarding future conditions in physical and human systems. As the focus on providing information about future climate for taking actions to cope with climate change, the science of uncertainty of climate change will develop more and more with the needs of decision makers in mind.